MDR-TB Patient’s Experience While Consuming Anti TB Drugs in Medan - Afiatika Ahsani; Dewi Elizadiani Suza; Amira Permatasari Tarigan (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Drug-resistant TB threatens global TB care and prevention. It remains a major public health problem in many countries. Nurses are front line personnel who have contact with patients, and because of their role as other medical care providers, in the prevention and monitoring of adverse drug reactions caused by Anti-TB Drugs to improve the quality of care. The aim of the study was to explore in depth the experiences of MDR TB patients taking anti-TB drugs. This type of research is qualitative with a descriptive phenomenological approach. There were 10 participants, selected by purposive sampling technique. Methods of data collection with in-depth interviews. The data were analyzed by the Colaizzi analysis method. The themes obtained were 7 themes, namely the psychological response of MDR TB patients, lifestyle of MDR TB patients undergoing treatment, side effects of anti-TB drugs that occur in MDR TB patients, efforts to overcome side effects, expectations of MDR TB patients, perceptions of MDR TB patients in consuming drugs. Anti-TB, and the support needed by MDR TB patients while taking Anti-TB drugs. Based on the results of the study, it is recommended that nurses provide nursing education related to the side effects of anti-TB drugs, treatment planning and information about things that may occur during treatment need to be emphasized so that patients and families can prepare physically and mentally to complete treatment.